A mechanistic review of chinese medicine polyphenols on bone formation and resorption - Li, Yan; Li, Lingyu; Li, Xiaoyun; Luo, Bingjie; Ye, Qianyun; Wang, Haoyu; Yang, Li; Zhu, Xiaofeng; Han, Li; Zhang, Ronghua; Tian, Huaqin; Wang, Panpan (Frontiers in Pharmacology, 2022)
Bone reconstruction includes a steady state system of bone formation and bone absorption. This tight coupling requires subtle coordination between osteoblasts and osteoclasts. If this balance is broken, it will lead to bone mass loss, bone density reduction, and bone metabolic diseases, such as osteoporosis. Polyphenols in Chinese herbal medicines are active ingredients in plant extracts with high safety and few side effects, and they can play a role in affecting bone formation and bone resorption. Some of these have estrogen-like effects and can better target bone health in postmenopausal women. The purpose of this review is to provide comprehensive information on the mechanisms underlying the relationship between traditional Chinese medicine (TCM) polyphenols and bone formation or bone resorption.